2010
DOI: 10.1093/jhered/esq097
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms within the Bovine DLK1-DIO3 Imprinted Domain Are Associated with Economically Important Production Traits in Cattle

Abstract: Previous studies show that DNA sequence variation within the mammalian DLK1-DIO3 imprinted domain influences production traits in domestic livestock, most notably the ovine callipyge phenotype. We assessed genotype-phenotype associations between 7 single nucleotide polymorphisms (SNPs) within the orthologous bovine DLK1-DIO3 domain and performance traits in 848 progeny-tested Holstein-Friesian dairy sires. One SNP (MEG3_01) located proximal to the maternally expressed 3 (MEG3/Gtl2) gene was associated with mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…In transgenic mice, skeletal muscle DLK1 is overexpressed, caused hypertrophy traits and affected muscle growth; similarly, a double muscled trait was caused in sheep (Davis et al, 2004;Magee et al, 2011;Bi and Kuang, 2012). In the present study, DLK1 expression was higher in the longissimus dorsi of males than in females at different growth stages after birth.…”
Section: Discussionsupporting
confidence: 55%
“…In transgenic mice, skeletal muscle DLK1 is overexpressed, caused hypertrophy traits and affected muscle growth; similarly, a double muscled trait was caused in sheep (Davis et al, 2004;Magee et al, 2011;Bi and Kuang, 2012). In the present study, DLK1 expression was higher in the longissimus dorsi of males than in females at different growth stages after birth.…”
Section: Discussionsupporting
confidence: 55%
“…The basis for this non-Mendelian effect on intrauterine growth remains unexplained, but increasing evidence strongly suggest that epigenetic inheritance involving imprinted genes is in play (Duselis et al, 2005; Jiang et al, 2007; Loschiavo et al, 2007; Cheverud et al, 2008; Hager et al, 2008; Wolf et al, 2008). Recently, a handful of known and putative imprinted genes have reportedly been associated with quantitative traits in beef cattle (Magee et al, 2010, 2011; Berkowicz et al, 2011; Chen et al, 2011; Sikora et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Most of the known imprinted genes were identified in mice and humans, and studies in other organisms primarily have confirmed the imprinting status of previously identified genes (12,13). However, studies in domestic livestock have revealed variation in normal phenotypes associated with imprinted genes for muscle growth and insulin-like growth factor-2 (IGF2) in pigs (14), for the delta-like 1 homolog (DLK) region in sheep (15), and for production traits in dairy cattle (16). In an investigation of horse, donkey, mule, and hinny pregnancies, peak serum concentrations of the placental hormone equine chorionic gonadotropin (eCG) were markedly higher when the sire was a horse than in pregnancies in which the sire was a donkey (17).…”
mentioning
confidence: 99%